SIZING PHOTOVOLTAIC SYSTEM IN DUHOK PROVINCE, KURDISTAN REGION OF IRAQ - KABAO, FARHAN K.; Omar, Omar S. (Science Journal of University of Zakho, 2023)
Using clean energy sources instead of traditional methods of energy production is important to tackle global warming and climate change. As in the rest cities of the Kurdistan Region and Iraq, the national electricity outage crisis continues in Duhok Governorate and the production of energy via different sources is still needed. This paper studies the simulation of two different types of solar energy systems on school roofs using the Homer Pro software. The first is a grid-connected system and the second, is an off-grid system for six different regions of Duhok Governorate, using the solar radiation data for each site. Our findings confirm the preference for on-grid PV over an off-grid PV system at all sites. As the cost of energy in USD per kWh in both grid-tied and stand-alone models varies from one region to another, which is as follows: Amedi (0.089, 0.339), Kani Masi (0.091, 0.0338), Bamarni (0.093, 0.338), Mangesh (0.095, 0.349), Semel (0.107, 0.341), and Akre (0.127, 0.347). The net present cost NPC in both grid-connected and grid-independent for 160 kW PV systems is as follows: Kani Masi ($217303, $260504), Amedi ($217621, $260710), Bamarni ($219007, $260587), Mangesh ($220167, $261239), Semel ($227566, $261222), and finally Akre ($238671, $262203).